2017
DOI: 10.1080/10717544.2017.1326539
|View full text |Cite
|
Sign up to set email alerts
|

Etodolac transdermal cubosomes for the treatment of rheumatoid arthritis: ex vivo permeation and in vivo pharmacokinetic studies

Abstract: In this study, transdermal etodolac-loaded cubosomes were developed in order to relieve patient pain and joints stiffness by providing stable etodolac concentration at the targeting sites through controlled drug delivery via the noninvasive skin route with more sustaining and less frequent dosing. Different ratios and percentages of poloxamer 407 and monoolein were used to formulate the cubosomes using emulsification and homogenization processes. The etodolac-loaded cubosomes showed particle size values rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 50 publications
9
46
0
Order By: Relevance
“…The DSC thermogram of clotrimazole exhibited a single sharp characteristic, endothermic peak at about 145 o C, corresponding to its melting point which was in agreement with that reported previously 44 .Such sharp peak indicates the crystalline state of the drug. However, the thermogram of clotrimazole loaded cubic gel revealed the disappearance of the drug melting peak and the appearance of endothermic peak at 71 o C. The disappearance of the drug melting peak indicating that the drug was molecularly encapsulated in the bicontinuous structures in non-crystalline form which was in agreement with that reported previously [45][46] .The appearance of endothermic peak at 71 o C in the thermograms of drug loaded cubic gel as well as blank cubic gel might be due to the phase transition from cubic to reversed hexagonal phase; such transition is known to occur at 71°C [47][48][49] . This finding can be also considered as further confirmation of formation of cubic phase in addition to polarized microscopy and TEM.…”
Section: Differential Scanning Calorimetry (Dsc) Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…The DSC thermogram of clotrimazole exhibited a single sharp characteristic, endothermic peak at about 145 o C, corresponding to its melting point which was in agreement with that reported previously 44 .Such sharp peak indicates the crystalline state of the drug. However, the thermogram of clotrimazole loaded cubic gel revealed the disappearance of the drug melting peak and the appearance of endothermic peak at 71 o C. The disappearance of the drug melting peak indicating that the drug was molecularly encapsulated in the bicontinuous structures in non-crystalline form which was in agreement with that reported previously [45][46] .The appearance of endothermic peak at 71 o C in the thermograms of drug loaded cubic gel as well as blank cubic gel might be due to the phase transition from cubic to reversed hexagonal phase; such transition is known to occur at 71°C [47][48][49] . This finding can be also considered as further confirmation of formation of cubic phase in addition to polarized microscopy and TEM.…”
Section: Differential Scanning Calorimetry (Dsc) Analysissupporting
confidence: 91%
“…All the investigated formulae(F3-F6)exhibited Newtonian flow behavior with viscosity values ranged from 2.36 ± 0.22 cp to 9.5 ± 0.15 cp as shown in Table 2. Such low viscosity values can increase drug penetration into skin 46 . Also, it can be noticed from comparing the viscosity values of formulae (F4, F5 & F6) that increasing the content of poloxamer 407in the dispersion led to increasing viscosity.…”
Section: Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that topical delivery of Etodolac via cubosomes provided controlled delivery at lower dosages but over a prolonged time period in comparison to orally administered Etodolac, and therefore could be a novel method for treating arthritis. [138] Capsaicin is a natural alkaloid used to treat psoriasis and contact allergies and as a formulation to relieve post-operative pain. Cubosomes formed from monoolein or phytantriol, stabilized with F127 and loaded with Capsaicin were used to test percutaneous skin permeation and Capsaicin retention in vitro on the abdominal skin of excised Sprague Dawley rats.…”
Section: Topical Treatmentmentioning
confidence: 99%
“…If the emulsion is o/w type then the addition of more continuous phase (water) will not cause cracking or separation of that emulsion. The results showed that the addition of water to all nanocubosomal dispersion formulas (F1-F10) showed clear nanocubosomal dispersion in less than 1 minute with no cracking or separation adding a further indication that they are all o/w type [27].…”
Section: Dilution Testmentioning
confidence: 93%